Implementasi penataan kelas formasi â€œuâ€ dalam rangka meningkatkan hasil belajar PKN pada materi sikap patuh pada tata tertib Siswa kelas III Min Baet - Munawar, Munawar (Universitas Serambi Mekkah, 2020)
The purpose of this class action research is to find out whether or not there is a significant influence on the arrangement of